2009
DOI: 10.1021/jm900056p
|View full text |Cite
|
Sign up to set email alerts
|

Novel Orally Bioavailable γ-Secretase Inhibitors with Excellent in Vivo Activity

Abstract: The development of potent gamma-secretase inhibitors having substituted heterocycles attached to a benzobicyclo[4.2.1]nonane core is described. This work led to the identification of [6S,9R,11R]-2',3',4',5,5',6,7,8,9,10-decahydro-2-(5-(4-fluorophenyl)-1-methylpyrazol-3-yl)-5'-(2,2,2-trifluoroethyl)spiro[6,9-methanobenzocyclooctene-11,3'-[1,2,5]thiadiazole] 1',1'-dioxide (16), which has excellent in vitro potency (0.06 nM) and which reduced amyloid-beta in APP-YAC mice with an ED(50) of 1 mg/kg (po). 16 had a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The APP selectivity of the sulfonamide core appears to be very sensitive to structural modifications. For example, potent and in vivo active (bicycle(4:2:1) nonane sulfamide GSI's [91,92], as well as 4-cyclohexyl sulfones [12,93] have been reported as equipotent on APP and Notch. Interestingly, despite equipotent inhibition of APP and Notch processing by gamma-secretase, sulfones are reported to be well tolerated at 3 mg/kg dose in a three- month treatment study in the Tg2576 mouse model [14], although higher doses were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…The APP selectivity of the sulfonamide core appears to be very sensitive to structural modifications. For example, potent and in vivo active (bicycle(4:2:1) nonane sulfamide GSI's [91,92], as well as 4-cyclohexyl sulfones [12,93] have been reported as equipotent on APP and Notch. Interestingly, despite equipotent inhibition of APP and Notch processing by gamma-secretase, sulfones are reported to be well tolerated at 3 mg/kg dose in a three- month treatment study in the Tg2576 mouse model [14], although higher doses were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…12) has excellent in vitro potency (0.06 nM), a good PK profile in three preclinical species, including 35-45% oral bioavailability, and lowered amyloid-b in APP-YAC mice for which oral administration afforded an ED 50 of 1 mg/kg. 37 Triperiden (Fig. 12) is an anti-influenza agent that is believed to inhibit viral infection through increase of the internal pH in the prelysosomal compartment.…”
Section: Miscellaneous Carbocyclic Bicyclo Systemsmentioning
confidence: 99%
“…4-Bromo-5-ethoxycarbonyl-1-methyl-2-(1-naphthyl)imidazole (17). A solution of n-BuLi in n-hexane (1.5 M, 1.1 equiv, 0.18 mL) was added dropwise to a solution of 4,5-dibromo-1-methyl-2-(1-naphthyl)imidazole (8e) (0.25 mmol, 92 mg) in anhydrous THF (0.5 M, 0.50 mL) under an argon atmosphere at −78 °C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%